L'expérience éducative des enfants travailleurs au Pérou : les écoles des NNATs - Alessandro Cussiánovich; Elvira Figueroa S. (Les éditions de la Maison des sciences de l'Homme, 2011)
This paper deals with the experience of schools for working children, the first one being founded 25 years ago. By first presenting briefly the movement of self-organization for working children (NNATs), it shows how the principles constituent of this movement were also applied to the running of these primary schools, which is based on the acknowledgement of working children as agents (co-protagonists) in the development of their country, on the pedagogy of tenderness, on the dignity of the working child and the positive synthesis between education and work. Secondly, after describing rapidly how these schools work, the paper explores the agents' point of view - children and teachers - concerning this experience, and shows how it impacts on the whole educational system in Peru, in a context of multiculturalism where the poorest people are also marginalized because they belong to indigenous communities. It then concludes by raising a series of theoretical and pedagogical questions.